2012
DOI: 10.1007/s10909-012-0574-y
|View full text |Cite
|
Sign up to set email alerts
|

Small Pitch Transition-Edge Sensors with Broadband High Spectral Resolution for Solar Physics

Abstract: We are developing small pitch transition-edge sensor (TES) X-ray detectors optimized for solar astronomy. These devices are fabricated on thick Si substrates with embedded Cu heat-sink layer. We use 35 × 35 µm 2 Mo/Au TESs with 4.5 µm thick Au absorbers. We have tested devices with different geometric absorber stem contact areas with the TES and surrounding substrate area. This allows us to investigate the loss of athermal phonons to the substrate. Results show a correlation between the stem contact area and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 18 publications
2
56
0
Order By: Relevance
“…By making these contact points small, the effects of athermal energy loss were minimized. 10 It was found that, for this geometry, the energy resolution degraded as the area of contact of the "stem contact" increased. The detector geometry with the smallest contact area between absorber and solid substrate was not only fast, but also demonstrated the best energy resolution seen by any low-temperature detector at 6 keV of 1.6 eV full width at half maximum (FWHM).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…By making these contact points small, the effects of athermal energy loss were minimized. 10 It was found that, for this geometry, the energy resolution degraded as the area of contact of the "stem contact" increased. The detector geometry with the smallest contact area between absorber and solid substrate was not only fast, but also demonstrated the best energy resolution seen by any low-temperature detector at 6 keV of 1.6 eV full width at half maximum (FWHM).…”
Section: Introductionmentioning
confidence: 93%
“…The energy loss from a thin film is given by the expression (10). If the source of x-rays is monoenergetic at a photon energy E 0 , then the lineshape is determined by the coordinate-dependent part of E loss (z 0 ).…”
Section: Modeling Spectral Lineshape In Mo/au Sensor For Mn K α Comentioning
confidence: 99%
See 1 more Smart Citation
“…For example, state-of-the-art TES X-ray detectors achieve an energy resolution of 1.58 eV FWHM at 5.9 keV [1]. Since TES are thermal detectors, they are in principle very broadband.…”
Section: Introductionmentioning
confidence: 99%
“…These devices [5][6][7][8] are made of square Mo(45 nm)/Au(200 nm) bilayers (Fig. 1a) and have transition temperatures of ∼100 mK.…”
Section: Introductionmentioning
confidence: 99%